Metacognitive Strategy Instruction for Appreciating English Literary Texts in a Second Language Context: An Investigation on G.C.E. Ordinary Level Classroom in a Semi-Government School in Kaluthara District - Wickramage, U.C.; Weerasinghe, B.A.I.R. (19th Conference on Postgraduate Research, International Postgraduate Research Conference 2018, Faculty of Graduate Studies,University of Kelaniya, Sri Lanka, 2018)
Distinct researchers have hypothesized about the teaching theories of literary interpretation. Yet, less recognition has been given to metacognitive awareness of literary interpretation process. This study aims at how metacognitive strategies can be applied explicitly in teaching and interpreting poetry in G.C.E. Ordinary Level classroom while focusing on critical and analytical thinking. The primary objective of the study reflects how the systematic implementation of metacognitive strategy instruction affects the critical and analytical thinking of the learner. 40 students of grade 10 in a semi-government school in Kaluthara district has been investigated by assigning them into an experimental group and a control group. 20 students have been assigned for each group. Three poems from the G.C.E. O/L Anthology have been selected from the category of Humor. Chamot & O'Malley’s (1994) Cognitive Academic Language Learning Approach (CALLA) is chosen to apply in the metacognitive strategy training. The metacognitive strategy instructions were implemented for the experimental group. Yet, a traditional teaching approach was administered for the control group. A pre-test and post-test which comprise essay typed questions based on the selected poems were administered. A quantitative data analysis approach was implemented where the analysis of the pre and post test scores of the experimental and control group were conducted using the SPSS software with statistical techniques including mean, standard deviation, frequencies and T-tests. The analysis of the posttest scores of the experimental group and control group does not indicate a statistically significant difference; t (14) = -0.506, p = 0.621. The analysis of the statistics of the pre and post-test of experimental group (within-group) depicts a statistically significant difference; t (14) = -7.6, p = 0.00. The statistical analysis of pre and post-tests of control group shows a slight statistically significant difference; t (14) = 2.7, p = 0.015. Thus, the study elucidates that the systematic implementation of metacognitive instructions enhances the critical thinking and analytical skills of the English literature learners in a second language context. In this regard, learning metacognitive strategy instruction is productive in English literature learning classroom
Keywords: Metacognitive Strategy Instruction; Literary Interpretation; Critical and Analytical Skills; English Literature; Second Language Context